Teachers' perception of attention deficit hyperactivity disorder and their knowledge of Strategies used for pupils with the disorder (2022)
Attention-Deficit Hyperactivity Disorder (ADHD) is one of the most frequent diagnoses in schools today, it is a common childhood neurodevelopment disorder that involves unremitting, and controversial childhood disorders, receiving large amounts of attention from researchers and general public. Pupils with this disorder have problems with attention span, impulse control and activity which frequently interfere with both classroom and social activities. The success of these categories of pupils in classroom situation depends on the ability of teachers to manage them. Despite the existence and availability of many empirical studies examining the causes, assessment, associated issues and treatment of ADHD, relatively few studies have examined teachers' perception of ADHD and their knowledge of support strategies used for pupils with the disorder. The extent to which this is done forms the basis of this study. A descriptive survey research was conducted, two hundred and thirty five pre-primary and primary school teachers participated in the research process where it was discovered that teacher hadpositive perception of the disorder and had low knowledge ofthe majority of the measured strategies used in handling pupils with ADHD. It was recommended that government and all private school owners should encourage the teachers through training for better implementation of strategies used for pupils with ADHD. Curriculum for teacher education should be restructured to include early childhood special education courses for pupils with special needs like ADHD.